THEORETICAL FOUNDATIONS, SOCIAL FACTORS, AND DEVELOPMENT MECHANISMS FOR FORMING HUMAN SPIRITUAL IMMUNITY IN THE CONTEXT OF INFORMATION THREATS AND GLOBALIZATION PROCESSES - Khurshid Ulmasjonovich Samatov; Yorqinbek Abduazizovich Ergashov (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
This article analyzes the impact of informatization and globalization processes on human consciousness, the theoretical foundations of the concept of spiritual immunity, the social factors that shape it, and the mechanisms for its development. The study scientifically examines the issues of protecting young people’s minds from various ideological threats in the modern information space. The theoretical foundations of spiritual immunity, its structural composition, and its significance in contemporary society are revealed. In addition, the article highlights the social factors influencing spiritual immunity and the effective mechanisms for its development. As a result of the research, it is substantiated that the mutual cooperation of the education system, family, and society is an important factor in the formation of spiritual immunity.